Management of Peripheral Neuropathy Secondary to Chronic Kidney Disease and Type 2 Diabetes - Nachiket Vidyanand Dixit; Mandip Goyal; Charmi Mehta (AYUSHDHARA, 2025)
Peripheral neuropathy is defined as a condition involving peripheral nervous system in which there is structural and functional damage to the peripheral nerves of sensory, motor, or mixed variety. In case of type 2 diabetes, most common neuropathy is DSPN (Distal Symmetric Polyneuropathy). Prevalence of diabetic neuropathy lies between 26 to 31%. This case report discusses the management of peripheral neuropathy in a 55-year-old male patient with type 2 diabetes and chronic kidney disease (CKD). The patient consuming oral hypoglycemic agents, presented with burning sensation and numbness in both lower limbs over three years and was classified as CKD stage G4. Patient was diagnosed as Madhumeha (type of Prameha caused due to Vata Dosha) according to Ayurveda and treated accordingly with Haritaki (Terminalia chebula)- two grams; Gokshura (Tribulus terrestris)-one gram; Pippali (Piper longum) -500 milligrams; Shweta Parpati- 500 milligrams three times after food with lukewarm water; Gokshuradi Guggulu two tablets three times before food with lukewarm water; Aragwadhadi Kwatha- 20ml and Vijaysaradi Kwatha- 20ml before food with lukewarm water and Guduchyadi Ksheerkashaya Yapana Basti (medicated enema prepared with milk decoction of Tinospora cordifolia) containing Madhu (honey)- 30gram; Saindhava Lavana (pink salt)- five grams; Guggulutiktaka Ghrita–30mililiter; Guduchi Siddha Ksheerkashaya (Tinospora cordifolia)- 200 milliliter for 14 days with Sarvanga Abhyanga with Bala Taila and Sarvanga Bashpa Swedana. Post-treatment, the patient exhibited significant symptom relief, and his CKD improved from stage G4 to G3b per risk assessment tools. This case highlights the potential of Ayurveda in managing diabetic neuropathy and CKD, emphasizing the need for further research on integrative approaches combining Shamana Chikitsa (conservative management) and Panchakarma therapies for chronic complications.